Narrative Learning in the Fifth Dimension - Hakkarainen, Pentti (Outlines. Critical Practice Studies, 2004)
The article describes an extension of the original idea of the fifth dimension model to pre-school age. We found out that small schildren are not able to use in their activity the tasks formulated by the adults. Learning tasks inbedded in different narratives were used in 5D environments. Experimental research lead to a hypothesis on the status of narrative learning as ”transitory activity system” between play and school learning. The hypothesis is presented and a transitory model sketched. Examples on children’s sense making and narrative learning in problem situations are are offered at the end of the article.